Construction of the only tunnel on the White Pass and Yukon Railroad, Tunnel Mountain, Alaska, approximately 1899. - Hegg, Eric A., 1867-1948 (1899)
Construction material being delivered to the tunnel's south portal. Caption on image: "Tunnel on the White Pass and Yukon RR" Original photograph by Eric A. Hegg 617; copied by Webster and Stevens 398.A.